ANALISIS VARIASI HARGA DAGING SAPI DI PROVINSI RIAU DAN DAERAH PEMASOK - Riauli Anggriani Pardede; Djaimi Bakce; Eliza Eliza (Program Studi Pendidikan Ekonomi Universitas Riau, 2018)
Demands of beef in Riau Province is increasing year by year, but not balance withthe production. Riau Province must imports the beef from other areas such asLampung Province, North Sumatera Province, West Sumatera Province, East JavaProvince and Australia. Ideally, the price changes in the supplier area would leadthe price changes in Riau Province. Thus, fluctuation of beef price in supplier areawill make fluctuation in Riau Province. The aim of this research is to analyze thebeef price variations in Riau Province and supplier areas in January 2006-Desember2015. Descriptive and Variation Coefficient analysis used to see the price dinamycand variation level. The result of the research shows that the beef price in RiauProvince and supplier areas were fluctuated and increasing. Variation coefficientshow that the beef price was stable, except in 2008. In 2008, the price was notstable caused by crisis of economi.